2022
DOI: 10.1038/s41529-021-00212-2
|View full text |Cite
|
Sign up to set email alerts
|

Marine Vibrio spp. protect carbon steel against corrosion through secreting extracellular polymeric substances

Abstract: The protection of marine materials against corrosion using marine bacterial biofilms is a promising strategy. However, little is known about the mechanisms of this attractive corrosion prevention method. In this work, the corrosion behaviors of X80 carbon steel (CS) in the presence of three different marine Vibrio species were studied. The results demonstrated that all the three Vibrio spp. displayed significant corrosion protection with a weight loss reduction of up to 68%. Moreover, their corrosion preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Furthermore, big capacitance arcs and one-wave peaks in Nyquist and Bode plots (Figure ) indicated that time constants such as protective film formation and charge-transfer process should be presented, and there are at least two similar relaxation times of time constants during the corrosion of A3 carbon steel. , As shown in Figure a–c, the semicircle diameter in the Nyquist plots was significantly larger than that without s-EPS (Figure a), indicating that the charge-transfer resistance and corrosion inhibition rate were increased with s-EPS . Additionally, by a comparation with Figure a′, the increased peak heights of Bode plots in Figure b′,c′ indicated that protective films were formed with the addition of s-EPS, leading to corrosion inhibition of A3 carbon steel in circulating cooling water …”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…Furthermore, big capacitance arcs and one-wave peaks in Nyquist and Bode plots (Figure ) indicated that time constants such as protective film formation and charge-transfer process should be presented, and there are at least two similar relaxation times of time constants during the corrosion of A3 carbon steel. , As shown in Figure a–c, the semicircle diameter in the Nyquist plots was significantly larger than that without s-EPS (Figure a), indicating that the charge-transfer resistance and corrosion inhibition rate were increased with s-EPS . Additionally, by a comparation with Figure a′, the increased peak heights of Bode plots in Figure b′,c′ indicated that protective films were formed with the addition of s-EPS, leading to corrosion inhibition of A3 carbon steel in circulating cooling water …”
Section: Resultsmentioning
confidence: 75%
“…35,36 As shown in Figure 5a−c, the semicircle diameter in the Nyquist plots was significantly larger than that without s-EPS (Figure 5a), indicating that the charge-transfer resistance and corrosion inhibition rate were increased with s-EPS. 17 Additionally, by a comparation with Figure 5a′, the increased peak heights of Bode plots in Figure 5b′,c′ indicated that protective films were formed with the addition of s-EPS, 33 leading to corrosion inhibition of A3 carbon steel in circulating cooling water. 37 The experimental data were fitted according to the actual situation; impedance spectra were analyzed using an equivalent circuit.…”
Section: Evaluation Of S-eps Anticorrosion Performance the Corrosion ...mentioning
confidence: 79%
See 2 more Smart Citations
“…EPS can adsorb on the metal surface and form a biofilm, which acts as a protective layer, hinders the transmission of oxygen, and separates a metal surface from a corrosive environment, thus, metal corrosion is inhibited [ 53 , 54 , 124 , 125 , 126 , 127 ]. The negatively charged functional groups in EPS, such as -NH 2 , -COOH, -C-O-C, and -OH, first adsorb positively charged metal ions to form complexes.…”
Section: Eps and Biocorrosionmentioning
confidence: 99%